Effect of air pressure on nanofiber production in solution blowing method - EKİCİ, BÜLENT; GÜL, MEHMET ZAFER; YANGAZ, MURAT UMUT; POLAT, YUSUF (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2020)
In this study, effect of air pressure on nanofiber diameter and morphology was studied for solution blowing technique. A computational fluid dynamics (CFD) analysis was realized via ANSYS (R) Fluent software, and the results were compared with experimental solutions. The results showed that an increase in air inlet pressure from 100 kPa to 300 kPa has significant effect on nanofiber diameter and morphology. In contrast, as the air inlet pressure increases above 300 kPa to 600 kPa, both nanofiber diameter increases, and the fiber agglomerations are observed due to high turbulence intensity. The droplets were observed at 100 kPa air inlet pressure due to low driving force applied to the polymer solution. The effects of air pressure on nanofiber diameter and morphology have been investigated by using finite volume method, and the results are compared with the experimental results.
Keywords: Solution blowing; nanofiber; finite volume method; air pressure; fluid dynamics